Anomalous depinning of magnetic domain walls within the ferromagnetic phase of the Weyl semimetal Co3Sn2S2. (1st February 2023) - Shen, Zihao; Zhu, X D; Ullah, Rahim R; Klavins, Peter; Taufour, Valentin
Abstract: We report bulk magnetization measurements and spatially resolved measurements of magnetic domains in C o 3 S n 2 S 2 single crystals. The results indicate that a previously reported magnetic anomaly around 130 K is due to an anomalous domain wall depinning upon cooling. Our measurements also reveal a hysteresis between field-cooled-cooling and field-cooled-warming magnetization curves acquired under a constant magnetic field below 300 Oe. This observation rules out the possibility that the anomaly stems from a second-order phase transition. Our results further suggest that changes in the shape of hysteresis loops from 5 to 170 K are caused by an unusual temperature-dependent domain nucleation field that changes sign around 130 K. The Kerr rotation images of the magnetic domains confirm that the domain walls depin between 120 and 140 K.